2007
DOI: 10.1098/rspb.2007.0457
|View full text |Cite
|
Sign up to set email alerts
|

Context matters: female aggression and testosterone in a year-round territorial neotropical songbird ( Thryothorus leucotis )

Abstract: Testosterone promotes aggressive behaviour in male vertebrates during the breeding season, but the importance of testosterone in female aggression remains unclear. Testosterone has both beneficial and detrimental effects on behaviour and physiology, prompting the hypothesis that selection favours an association between aggression and testosterone only in certain contexts in which intense or persistent aggression may be beneficial. We tested this hypothesis in a year-round territorial female buff-breasted wrens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…The importance of female aggression in shaping social and reproductive parameters linked to large-scale population processes has started to gain increased attention (Sandell & Smith 1997;Gill et al 2007;Sandell 2007;Smith & Blumstein 2008). However, to date, few studies have elucidated patterns of observed consistent individual differences in female aggression, and how this behavioural consistency may impact on an individual's social and reproductive strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of female aggression in shaping social and reproductive parameters linked to large-scale population processes has started to gain increased attention (Sandell & Smith 1997;Gill et al 2007;Sandell 2007;Smith & Blumstein 2008). However, to date, few studies have elucidated patterns of observed consistent individual differences in female aggression, and how this behavioural consistency may impact on an individual's social and reproductive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Female aggression, on the other hand, is assumed to be either subtle or inconspicuous and has received relatively little attention (Gill et al 2007). Recent work, however, suggests that female aggression may have important consequences in a number of functional contexts (Dunn & Hannon 1991;Slagsvold & Lifjeld 1994;Rosvall 2008), such as territory acquisition and eviction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in some species aggression is unchanged [3,6,13] or even increased [12,17,18] during the non-breeding season. For example, aggression persists during the non-breeding season in song sparrows, Melospiza melodia morphna [16], and is further elevated in Siberian hamsters, P. sungorus [17,18].…”
Section: Introductionmentioning
confidence: 94%
“…Numerous studies have demonstrated a positive relationship between gonadal steroids, particularly testosterone (T), and aggression in males and females of many vertebrates, including birds, lizards and mammals (e.g. [3][4][5][6]). Traditionally, these studies have focused on males in reproductive condition, often in laboratory animals such as rats and mice (reviewed in [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Average intra-assay coefficient of variation was not determined, but ranges between 2 and 16 per cent in our laboratory for this kind of assay (e.g. Gill et al 2007). Average inter-assay coefficient of variation was 24.6 per cent.…”
mentioning
confidence: 99%